Ecotourism as a strategy for the promotion of environmental awareness the case of the Tampisaw festival in Concepcion, Iloilo - Nacionales, Jose P. (2005.)
A one-month study period from January to February 2005 was conducted from five (5) out of eighteen (18) coastal barangays in the municipality of Concenpcion to find out whether " Tampisaw Festival" is an effective ecotourism strategy to raise environmental awareness among the residents. A survey was made using questionnaires with answers to one hundred and forty (140) respondents representing different sectoral communities. The present status of the ecotourism program was examined based on secondary data sourced-out from the Local Government Unit (The Municipal Tourism Master Plan, the Aquatic and fisheries Resources Database and other data). Results from the interview showed majority of the respondents understood the objectives of the festival, the activities and natural attractions it showcased in relation with environmental protection and natural resource conservation. The problems identified by respondnets are consistent with the real problems existing as examined, and two stood out - the lack of local and national funding support and the change in political leadership that can affect the festival's sustainability. The festival as an ecotourism strategy has succeeded in raising the environmental awareness of the residents but the ecotourism program of the municipality faces a challenge in making the program sustainable. The transitory status (informal organizational set-up attached to the Office of the Mayor) of the Culture, History, Arts and Tourism (CHAT) Council mandated to operationalize the ecotourism program may not ensure its sustainability since it is co-terminus with the local chief executive. Since the problem by nature is institutional, one remarkable recommendation for this study is to institutionalize the CHAT Council by creating a separate office equipped with skilled ecotourism staff, hence, it can effectuate proper planning and coordination with the communities involved towards promotion, development and enhancement of ecotourism along with an effective strategy to strengthen fund sourcing to realize the programs and projects embedded in the Municipal Tourism Master Plan.
Special Problem (MMA). -- Miagao, Iloilo : University of the Philippines in the Visayas, March 2005.